A platform for high-throughput screening of DNA-encoded catalyst libraries in organic solvents - Hook, K. Delaney (Royal Society of Chemistry, 2017)

(untitled) (Chem Sci)
We have developed a novel high-throughput screening platform for the discovery of small-molecules catalysts for bond-forming reactions. The method employs an in vitro selection for bond-formation using amphiphilic DNA-encoded small molecules charged with reaction substrate, which enables selections to be conducted in a variety of organic or aqueous solvents. Using the amine-catalysed aldol reaction as a catalytic model and high-throughput DNA sequencing as a selection read-out, we demonstrate the 1200-fold enrichment of a known aldol catalyst from a library of 16.7-million uncompetitive library members.